2019
DOI: 10.21873/invivo.11715
|View full text |Cite
|
Sign up to set email alerts
|

Primary Hemangiopericytoma Arising in Extralobar Pulmonary Sequestration: A Coincidence or Two Rare Disorders?

Abstract: Background/Aim: Extralobar pulmonary sequestration (EPS) is an unusual congenital defect characterized by the presence of non-functioning lung tissue receiving arterial supply from the systemic arteries. Primary hemangiopericytoma (HPC) is an uncommon potentially malignant tumor of vascular origin that usually involves the soft tissue of the extremities or retroperitoneum, but extremely rarely affects the lung. We present the rare case of a primary pulmonary HPC arising in an EPS. Case Report: A 65-yearold wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Choe et al 15 reported ELS torsion occurred in a 10‐year‐old boy with hemorrhagic infarction led to acute abdominal pain and fever. The Christos group confirmed that primary pulmonary hemangiopericytoma may arise in ELS 3 . Thus, the conservative treatment of ELS has potential risks to some extent.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Choe et al 15 reported ELS torsion occurred in a 10‐year‐old boy with hemorrhagic infarction led to acute abdominal pain and fever. The Christos group confirmed that primary pulmonary hemangiopericytoma may arise in ELS 3 . Thus, the conservative treatment of ELS has potential risks to some extent.…”
Section: Introductionmentioning
confidence: 97%
“…ILS shares visceral pleura with the adjacent normal lung lobe. In contrast, ELS has its own visceral pleura outside the normal lung, which accounts for approximately 14%–25% of PS 1–3 . The majority of ELS are located in the thoracic cavity, especially near the lower lung lobes and spine.…”
Section: Introductionmentioning
confidence: 99%